2020
DOI: 10.15835/nbha48311834
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ecophysiological characteristics of tomato (Lycopersicon esculentum L.) in response to organic fertilizers (compost and vermicompost)

Abstract: The organic fertilizers such as urban wet-waste compost and vermicompost can improve the physicochemical properties of soil and have a favourite effect on plants growth due to the high nutrient content, high water holding capacity, plant growth regulators, and beneficial microorganisms. In this regard, this study was conducted to evaluate the organic fertilizer mixture on the physiological and morphological indices of tomato seedlings under greenhouse conditions. The experiment was done as factorial in a compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…In another experiment, Ref. [65] stated that the simultaneous application of compost and vermicompost enhanced the MSI under salinity stress and attributed this increase to the regulation of membrane integrity, as well as the prevention of plasma membrane damage [66]. Aslam et al [67] also reported similar results where they explained that the application of vermicompost increased membrane stability in tomatoes, as evidenced by increased MSI percentage in the treated plants.…”
Section: Plant Growth Yield Physiology and Nutritional Quality Attrib...mentioning
confidence: 83%
“…In another experiment, Ref. [65] stated that the simultaneous application of compost and vermicompost enhanced the MSI under salinity stress and attributed this increase to the regulation of membrane integrity, as well as the prevention of plasma membrane damage [66]. Aslam et al [67] also reported similar results where they explained that the application of vermicompost increased membrane stability in tomatoes, as evidenced by increased MSI percentage in the treated plants.…”
Section: Plant Growth Yield Physiology and Nutritional Quality Attrib...mentioning
confidence: 83%
“…This can be attributed to plant growth regulators such as auxin. Ahmadpour and Armand (2020) stated that Zinc (Zn) is an important element from vermicompost and plays an important role in the structure of Tryptophan Amino Acid (the main precursor to the auxin synthesis). Auxin can increase cell walls that lead to an increase in the longitudinal growth of the plant.…”
Section: Leaf Numbersmentioning
confidence: 99%
“…According to Ahmadpour and Armand (2020), increasing the leaf area shows more photosynthetic capacity. There is a direct relationship between the photosynthetic system to dry matter yield.…”
Section: Leaf Areamentioning
confidence: 99%
See 1 more Smart Citation